Chapterhouse: Dune - Herbert, Frank (Herbert, Frank. Dune chronicles, 2020)
Fifteen thousand years after Leto II's death, the remnants of the Bene Gesserit contend with the ruthless leaders of an alien culture to forge a new civilization and preserve the best of the Old Empire.